Deputation to the Minister of Health - National Anti-Vaccination League (Great Britain) (London : National Anti-Vaccination League)
1929 1920s 12 pages ii THE VACCINATION INQUIRER - (Supplement) August. The late Alfred Russel Wallace said "the abolition of all laws enforcing or encouraging vaccination is of more immediate and vital importance than any party dogma or any political programme." That is our view. We hope that it is or will become yours. Before Jenner, the medical profession practised and believed in the inoculation of smallpox direct. By persuading the Government of the day that vaccination would protect for life, a statement the falsehood of which he later admitted himself, Jenner got £30,000. In that belief the Vaccination Acts of 1853 and 1867 were passed. Every doctor now knows the claim to be untrue, and that fact destroys at once any justification that ever existed for passing those Acts. The limit of protection now claimed is by some seven years, by others two, and by the French Government apparently two months, that being the period within which English passengers into France had to qualify for admission during the recent scare. Moreover, since those Acts were passed dangerous after-effects have been discovered which, if then known, most likely would have prevented their enactment. In 1922, Professors Mcintosh, of Middlesex Hospital, and Turnbull, of London Hospital, published in the "British Journal of Experimental Pathology" proof that they had found vaccination to be a direct cause of encephalo-myelitis. Two committees appointed by this country and one by the League of Nations Health Organisation have investigated this dreadful disease and verified the findings of the two eminent English pathologists. Following many similar post-vaccinal cases in Holland, the Dutch Government have suspended compulsion for two years. One result of these inquiries is a recommendation — not to discontinue this dangerous operation — but to change its form. Four marks were till now held necessary for protection. Now only one is recommended. The vaccine that was safe and effective, is now to be diluted. You are to increase the protection by decreasing the protective. Better do away with the danger by dispensing altogether with its cause. It is thirty years since the Royal Commission investigated this question. One result of its report was the Conscience Clause of the Conservative Act of 1898, a clause administered so harshly that it led to the substitution of a Statutory Declaration in the Liberal Act of 1907. Under that Act more than half the children born in this country are saved by their parents the infliction of this disease. If self-government is to be a reality, surely this virtual referendum justifies our demand that their will shall prevail. We recognise that medical opinion is against us now, and your medical advisers will tell you the orthodox view. But, like other orthodoxies, medical orthodoxy is both fallible and changeable. Were it not, we should still be killing fever patients by blood-letting, retarding recovery from all sorts of illness by huge doses of alcohol, now discredited and discarded in all our hospitals ; and instead of vaccination we should still be inoculating smallpox to prevent smallpox, a practice made penal 76 years ago. And medical opinion on vaccination is changing. From this pamphlet you will see that even orthodox believers in its efficacy doubt the wisdom of compulsion. Dr. Walter Carr, in his Presidential Address, asked the Medical Society of London as recently as last October "whether the present form of smallpox is worth being protected against, and suggested that our views about vaccination would change even more quickly than now had it not become part of the official creed, established by law, and therefore as dogmatic and as difficult to alter as the Athanasian Creed itself." Even Medical Officers of Health, those most directly and professionally interested in public health, are coming round to that view. I quote only one, and that because he is Medical Officer of Health of the borough in which I live. Dr. R.P. Garrow, now Medical Officer of Health for Hornsey, formerly Medical Officer of Health for Chesterfield, boldly told the same meeting that he had been cured of any views he had ever held about the advisability of compulsory vaccination. But proof as to its value is to be found not in opinion, medical or other, but in statistics and experience, of which laymen are equally competent to judge. Here are some facts I ask you to note :— 1. In our own history we had most smallpox when we had most vaccination. The greatest prevalence preceded 1898, and the worst epidemic was in 1871-2, at a period when vaccinations were 85 per cent. of births, and when 42,000 deaths occurred in two years. The most terrible outbreak of late years, which carried off no less than 60,000, was in the well-vaccinated Philippines. 2. As exemptions have increased deaths have declined until they have almost disappeared. Since 1907, which multiplied exemptions, deaths have never exceeded 1 per million of population. 3. During the 20 years prior to that date 9,855 died of smallpox in England and Wales, averaging 492 per annum. During the 20 years following deaths were 292 in all, or 14 per annum, i.e., the 20 years' total after was 200 fewer than one year's average before 1907. Since 1904 there has 36/H24/24